Semiotics Analysis on the Novel Night on the Galactic Railroad By Miyazawa Kenji Using Charles Sanders Peirce’s Triadic Model - Ananda Jan Wiyogo; Sonya Ayu Kumala (e-LinguaTera, 2023)
This reserach about the semiotic analysis in the novel “Night on The Galactic Railroad” written by Miyazawa Kenji in 1927. The writer wrote this thesis in order to find the sign inside the Novel and interpret the signs using Peirce’s theory by using a Triadic Model. The author decided to further ease the process of interpreting the sign by using Peirce’s triadic model. The writer decided to use qualitative method to find the result for this research. The writer used 2 objects for this research, formal and material object. The formal object being the Charles Sanders Peirce’s theory. While the material object being the Novel Night on The Galactic Railroad by Miyazawa Kenji. The novel was written in 1927 and published by Bunpoudou in 1934. The writer used a note taking method in this research as an instrument. The writer used Peirce’s theory to analyze the data. The consideration of choosing Pierce because this theory can cover all level in semiotics process of meaning interpretation. Based on the analysis process, the writer found that there are 24 signs, which is 17 indexes, 5 symbols, and 2 icons. The writer concludes that the most frequent signs found in the novel are indexes.